Diurnal intraocular pressure fluctuation in black adult primary open angle glaucoma patients attending Ruharo Eye Centre, South- Western Uganda - Arunga, S.; Bwetsia, F. M.; Aliraki, L. (East African Journal of Ophthalmol Central and Southern Africa, 2014)
To study the general diurnal intraocular pressure (IOP) fluctuation in black adult patients with Primary Open Angle Glaucoma attending Ruharo Eye Centre; to determine their IOP fluctuation range and determine their 24 hour IOP fluctuation pattern. Design: Descriptive cross sectional study. Methods: This was a hospital based, descriptive cross sectional study. Fifty one patients with glaucoma on different treatment options (No treatment, medical treatment and post trabeculectomy) were enrolled and intraocular pressure measured every 2 hours for 24 hours. The mean fluctuation ranges, peak and trough times of intraocular pressure were recorded for each group and 24 hour fluctuation curve patterns were drawn. Results: Primary Open Angle Glaucoma (POAG) patients who were not on treatment had the highest mean intraocular pressure fluctuation range 11.1mmHg (95% CI 8.3-14) followed patients on medical treatment who had the second highest mean fluctuation range 9.3mmHg (95% CI 7.5-11.1), while patients who had received trabeculectomy had the lowest mean IOP fluctuation ranges 5.3 (95% CI 3.5-7.0). The general average peak intraocular pressure time was between 11am-1pm. Conclusion: Trabeculectomy was found to have the best control of IOP fluctuation in patients with POAG compared to medical treatment (timolol, pilocarpine and acetazolamide) and those not on treatment. The best time for measuring IOP in patients with POAG was found to be between 11am-1pm because most of the peaks IOPs were captured during this time.
Keywords: Diurnal intraocular pressure; Glaucoma patients; Ruharo Eye Centre